TO MONITOR THE ADVERSE DRUG REACTIONS ASSOCIATED WITH THE USE OF ANTIHYPERTENSIVE AGENTS IN A TERTIARY CARE HOSPITAL IN CENTRAL KERALA - ASHIN T SENOJ; SANTOSH PILLAI; SAJIT VARGHESE; NISHA KURIAN; JITHIN YESUDAS; JOMON S JOHN; LIYA ROSLIN JOSEPH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to monitor the adverse drug reactions (ADRs) due to anti-hypertensive drugs prescribed in a tertiary care hospital. Methods: The study was conducted in the outpatient department of General Medicine of a tertiary care hospital in Kerala. The demographic details and suspected ADRs were collected from the patients and evaluated, and causality assessment was done. Results: More women developed ADRs compared to men due to the anti-hypertensive drug. The occurrence of adverse reactions was seen to be more in older patients over 50 years of age compared to younger individuals. The occurrence of ADR was more in patients using a combination of drugs (74.3%) rather than monotherapy. Calcium channel blockers were associated with more number of adverse reactions (62.5%) with amlodipine showing the maximum ADRs (64.8). The commonly seen ADR was edema. When the causality assessment was done, most were probable/likely followed by possible. Conclusion: This study shows that calcium channel blockers were the therapeutic class of drugs that caused the most number of ADRs, especially pedal edema; there was a higher frequency of ADRs to various antihypertensive drugs. Females and those more than 50 years old had shown a higher proportion of ADRs though not statistically significant. Furthermore, those individuals who took more drugs to treat hypertension also showed more ADRs. This study of adverse reactions toward antihypertensive medications will help physicians to choose a better option to treat their patients which will eventually help in patient satisfaction and medication safety.